Question
upstudy study bank question image url

Evaluate the integral. \[ \int_{0}^{3} \frac{x^{2}+x+1}{(x+1)^{2}(x+2)} d x \]

Ask by Carter Cummings. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The integral evaluates to \( \frac{3 + 4\ln\left(\frac{125}{128}\right)}{4} \).

Solution

Calculate the integral \( \int_{0}^{3} \frac{x^{2}+x+1}{(x+1)^{2}(x+2)} d x \). Evaluate the integral by following steps: - step0: Evaluate using formulas and rules: \(\int_{0}^{3} \frac{x^{2}+x+1}{\left(x+1\right)^{2}\left(x+2\right)} dx\) - step1: Evaluate the integral: \(\int \frac{x^{2}+x+1}{\left(x+1\right)^{2}\left(x+2\right)} dx\) - step2: Rewrite the fraction: \(\int \left(\frac{1}{\left(x+1\right)^{2}}-\frac{2}{x+1}+\frac{3}{x+2}\right) dx\) - step3: Use properties of integrals: \(\int \frac{1}{\left(x+1\right)^{2}} dx+\int -\frac{2}{x+1} dx+\int \frac{3}{x+2} dx\) - step4: Evaluate the integral: \(\frac{\left(x+1\right)^{-1}}{-1}+\int -\frac{2}{x+1} dx+\int \frac{3}{x+2} dx\) - step5: Evaluate the integral: \(\frac{\left(x+1\right)^{-1}}{-1}-2\ln{\left(\left|x+1\right|\right)}+\int \frac{3}{x+2} dx\) - step6: Evaluate the integral: \(\frac{\left(x+1\right)^{-1}}{-1}-2\ln{\left(\left|x+1\right|\right)}+3\ln{\left(\left|x+2\right|\right)}\) - step7: Rewrite the expression: \(-\frac{1}{x+1}-2\ln{\left(\left|x+1\right|\right)}+3\ln{\left(\left|x+2\right|\right)}\) - step8: Add the terms: \(-\frac{1}{x+1}+\ln{\left(\frac{\left|x+2\right|^{3}}{\left(x+1\right)^{2}}\right)}\) - step9: Return the limits: \(\left(-\frac{1}{x+1}+\ln{\left(\frac{\left|x+2\right|^{3}}{\left(x+1\right)^{2}}\right)}\right)\bigg |_{0}^{3}\) - step10: Calculate the value: \(\frac{3+4\ln{\left(\frac{125}{128}\right)}}{4}\) The integral of the given function from 0 to 3 is \(\frac{3+4\ln{(\\frac{125}{128})}}{4}\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To evaluate the integral \[ I = \int_{0}^{3} \frac{x^{2}+x+1}{(x+1)^{2}(x+2)} \, dx, \] we can begin by simplifying the integrand through partial fraction decomposition. We will express \[ \frac{x^2 + x + 1}{(x+1)^2 (x+2)} \] as a sum of simpler fractions. We want to find constants \( A \), \( B \), and \( C \) such that \[ \frac{x^2 + x + 1}{(x+1)^2 (x+2)} = \frac{A}{x+1} + \frac{B}{(x+1)^2} + \frac{C}{x+2}. \] Multiplying both sides by the denominator \( (x+1)^2 (x+2) \) gives: \[ x^2 + x + 1 = A(x+1)(x+2) + B(x+2) + C(x+1)^2. \] Expanding the right-hand side: 1. \( A(x+1)(x+2) = A(x^2 + 3x + 2) = Ax^2 + 3Ax + 2A \) 2. \( B(x+2) = Bx + 2B \) 3. \( C(x+1)^2 = C(x^2 + 2x + 1) = Cx^2 + 2Cx + C \) Combining these, we have: \[ (A+C)x^2 + (3A + B + 2C)x + (2A + 2B + C). \] Setting the coefficients equal to those in \( x^2 + x + 1 \): 1. For \( x^2 \): \( A + C = 1 \) 2. For \( x \): \( 3A + B + 2C = 1 \) 3. For the constant: \( 2A + 2B + C = 1 \) Now we can solve this system of equations. From the first equation, we can express \( C = 1 - A \). Substituting \( C \) into the other two equations gives: For the second equation: \[ 3A + B + 2(1 - A) = 1 \implies 3A + B + 2 - 2A = 1 \implies A + B = -1 \quad (1) \] For the third equation: \[ 2A + 2B + (1 - A) = 1 \implies 2A + 2B + 1 - A = 1 \implies A + 2B = 0 \quad (2) \] We now have a system of two equations: 1. \( A + B = -1 \) 2. \( A + 2B = 0 \) Subtract the first from the second: \[ (A + 2B) - (A + B) = 0 - (-1) \implies B = 1. \] Substituting \( B = 1 \) back into \( A + B = -1 \): \[ A + 1 = -1 \implies A = -2. \] Finally, substituting \( A \) back to find \( C \): \[ C = 1 - A = 1 - (-2) = 3. \] The partial fraction decomposition is: \[ \frac{x^2 + x + 1}{(x+1)^2 (x+2)} = \frac{-2}{x+1} + \frac{1}{(x+1)^2} + \frac{3}{x+2}. \] Now, we can split the integral: \[ I = \int_{0}^{3} \left( \frac{-2}{x+1} + \frac{1}{(x+1)^2} + \frac{3}{x+2} \right) dx. \] Calculating each integral separately: 1. \[ \int \frac{-2}{x+1} \, dx = -2 \ln|x+1| + C. \] 2. \[ \int \frac{1}{(x+1)^2} \, dx = -\frac{1}{x+1} + C. \] 3. \[ \int \frac{3}{x+2} \, dx = 3 \ln|x+2| + C. \] Combining these, we have: \[ I = \

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy